Reinventing fast charging: developing and validating NLV algorithm for Li-ion batteries - Chng, Joseph (Nanyang Technological University, 2024)
In response to the soaring demand for Li-ion batteries, our project introduces a groundbreaking approach to fast charging, centered around the NLV (Nonlinear Voltammetry) fast charging algorithm. With optimal software design considerations in mind, we have developed a new application for comprehensive testing of batteries from around the world. This includes the demonstration and validation of the NLV algorithm, which outperforms the current industrial method known as CCCV (Constant Current Constant Voltage). Extensive battery testing was conducted to determine crucial algorithm variables and ensure temperature and health preservation during charging. The resulting software boasts a robust architecture adhering to key software design principles, integrating safety measures like a kill switch and temperature limits for the battery, usually 55°C. Battery testing includes testing of NLV algorithm on various type of lithium ion batteries with different chemical composition to prove that this algorithm is generalized for most of the lithium ion batteries. Moreover, our study highlights the urgent need for superior charging methods, particularly in industries requiring faster charging times for power tools and electric vehicle batteries. By demonstrating the suitability of the NLV algorithm for rapid charging cells such as the Samsung 30T and 40T, while upholding safety and performance standards, this project underscores its potential for widespread adoption as it shows a much more adaptive and efficient approach can be used for battery charging without the neglect of safety measures and battery health.